2015
DOI: 10.3928/01477447-20151123-07
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Knee Dislocation After Total Knee Arthroplasty

Abstract: Knee dislocation after total knee arthroplasty (TKA), although rare, is a dangerous injury that can lead to neurovascular compromise and permanent disability. Chronic dislocation after TKA is even less common and is defined as dislocation that is present for 4 weeks or more. There are few reports of its management. Chronic dislocation may be complicated further by concomitant extensor mechanism disruption, ligamentous instability, and/or capsular contracture. This article describes 3 cases of chronically dislo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Chronic dislocation of primary TKA, defined as being older than 4 weeks [ 13 ], is even more uncommon, and can be further complicated by marked instability, fixed angular deformity, extensor mechanism disruption, severe bone loss, and infection, as in our case. Ross et al [ 13 ] reported 3 cases of chronic posterior primary TKA dislocations; 2 of them had BMI >40, all requiring a higher level of constraint to maintain knee stability, and an extensor mechanism allograft was needed in 2 of them.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Chronic dislocation of primary TKA, defined as being older than 4 weeks [ 13 ], is even more uncommon, and can be further complicated by marked instability, fixed angular deformity, extensor mechanism disruption, severe bone loss, and infection, as in our case. Ross et al [ 13 ] reported 3 cases of chronic posterior primary TKA dislocations; 2 of them had BMI >40, all requiring a higher level of constraint to maintain knee stability, and an extensor mechanism allograft was needed in 2 of them.…”
Section: Discussionmentioning
confidence: 92%
“…Chronic dislocation of primary TKA, defined as being older than 4 weeks [ 13 ], is even more uncommon, and can be further complicated by marked instability, fixed angular deformity, extensor mechanism disruption, severe bone loss, and infection, as in our case. Ross et al [ 13 ] reported 3 cases of chronic posterior primary TKA dislocations; 2 of them had BMI >40, all requiring a higher level of constraint to maintain knee stability, and an extensor mechanism allograft was needed in 2 of them. Chu et al [ 12 ] reported a posterior TKA dislocation in a 54-year-old woman with septic TKA, which was treated initially with debridement and antibiotic beds; she had the dislocation 11 days after surgery as a result of posterior cruciate ligament tearing due to infection.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, several case reports have identified obesity as the direct cause of post-TKA dislocation [ 10 ]. It correlates with poorer muscle quality and a greater risk of medial collateral ligament avulsion [ 3 , 5 ]. The mean BMI of patients with tibiofemoral dislocation after TKA has been reported at 33 kg/m 2 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, among aged populations, cases of total knee arthroplasty (TKA) for knee OA with permanent patellar dislocation [11] or lateral patellar dislocation after TKA are often reported [12, 13]. Accordingly, the authors concluded that the causes of lateral dislocation of the patella after TKA are component malpositions of an anterior, internally rotated, and medial femur; internally rotated tibia; and lateral patella.…”
Section: Discussionmentioning
confidence: 99%